Dual-layer aligned-random nanofibrous scaffolds for improving gradient microstructure of tendon-to-bone healing in a rabbit extra-articular model - Cai J (Dove Medical Press, 2018)
Jiangyu Cai,1,* Juan Wang,2,* Kaiqiang Ye,2 Dandan Li,2 Chengchong Ai,1 Dandan Sheng,1 Wenhe Jin,1 Xingwang Liu,1 Yunlong Zhi,1 Jia Jiang,1 Jun Chen,1,3,4 Xiumei Mo,2 Shiyi Chen1 1Department of Sports Medicine, Huashan Hospital, Fudan University, Shanghai 200040, China; 2State Key Laboratory for Modification of Chemical Fibers and Polymer Materials, College of Chemistry, Chemical Engineering and Biotechnology, Donghua University, Shanghai 201620, China; 3Shanghai BJ-KMC Medical Technology Co., Ltd, Shanghai 201707, China; 4State Key Laboratory of Molecular Engineering of Polymers, Fudan University, Shanghai 200433, China *These authors contributed equally to this work Background: Tendon/ligament injuries are common sports injuries. Clinically, the repair of a ruptured tendon or ligament to its bony insertion is needed, but the enthesis structure is not well reestablished following surgical repair. Herein, we fabricated dual-layer aligned-random scaffold (ARS) by electrospinning and aimed to investigate the effect of the scaffold on tendon-to-bone healing in vivo. Materials and methods: The random and dual-layer aligned-random silk fbroin poly(L-lactic acid-co-e-caprolactone) (P(LLA-CL)) nanofibrous scaffolds were successfully fabricated by electrospinning methods. Ninety New Zealand white rabbits were randomly divided into three groups (random scaffold [RS], ARS, and control groups), and they were subjected to surgery to establish an extra-articular tendon-to-bone healing model with autologous Achilles tendon. Results: Histological assessment showed that the ARS significantly increased the area of metachromasia, decreased the interface width, and improved collagen maturation and organization at the tendon–bone interface compared with the RS and control groups. Microcomputed tomography analysis showed that the bone tunnel area of RS and ARS groups was significantly smaller than those of the control group. Real-time polymerase chain reaction showed that BMP-2 and osteopontin expression levels of the tissue at the interface between the bone and graft in the RS and ARS groups were higher than those of the control group at 6 weeks. Collagen I expression level of the ARS group was significantly higher than those of the RS and control groups at 6 and 12 weeks. Moreover, the ARS groups had a better ultimate load-to-failure and stiffness than the RS and control groups. Conclusion: ARS could effectively augment the tendon-to-bone integration and improve gradient microstructure in a rabbit extra-articular model by inducing the new bone formation, increasing the area of fibrocartilage, and improving collagen organization and maturation. The dual-layer aligned-random silk fibroin/P(LLA-CL) nanofibrous scaffold is proved to be a promising biomaterial for tendon-to-bone healing. Keywords: tendon-to-bone healing, electrospinning, aligned, random, dual-layer